(untitled) (Heritage, 2023)
This paper analyzes the poetics of Grigorije Božović’s travel literature, focusing on his attitude towards folk traditions in particular. A special emphasis is put on a metaphorical potential of the concept of "epic" in his travelogues, as opposed to Emil Staiger’s concept of "epic" as well as other literary genres, mainly folklore. Further analysis encompasses the notion of epic man, the concept of tradition introduced by Thomas Stearns Eliot and it also explores the relationship between tradition and contemporaneity in Grigorije Božović’s travel writings.